PENGARUH PERBAIKAN TANAH FONDASI DAN PERKUATAN TERHADAP STABILITAS LERENG TIMBUNAN JALAN DI ATAS TANAH LUNAK - Zul Aslam; Nurly Gofar (Universitas Kristen Maranatha, 2022)
The construction of toll roads in South Sumatra faces two problems. First, most of the road sections are built on soft soil deposits, so the soil must be improved to speed up consolidation process and to improve bearing capacity. Second, the embankment required to reach the design elevation of the toll road is quite high so that reinforcement is needed to improve slope stability. This paper contains the results of a study on the effect of soil improvement using PVD and vacuum pressure, installation of geotextile layers and pile at the toe of embankment slopes, on the stability of the embankment. The analysis were carried out using data obtained from the construction of the Kayu Agung – Palembang toll road Section 1A, including geometry data, soil stratification, and configuration of PVD installation and soil reinforcement. Slope stability analysis was carried out using the Morgenstern & Price method which is integrated in SLOPE/W program. The results of the analysis show that the safe embankment height for the original soil condition is 3.5 m while the required height of embankment was 6 m. Analysis made for the 6 m high embankment using soil properties after ground improvement with PVD and vacuum pressure shows the FoS is still below 1.5. The presence of geotextile layers and pile improved the performance of the embankment and increased the FoS to 2.410. The slope is still in a safe condition with FoS of 1.762 after the construction of toll road and traffic load which induces a combined load of 35 kPa.